Mutation profile of high‐grade appendiceal mucinous neoplasm. Issue 3 (23rd December 2019) - Liao, Xiaoyan; Vavinskaya, Vera; Sun, Katherine; Hao, Yansheng; Li, Xiaodong; Valasek, Mark; Xu, Ruliang; Polydorides, Alexandros D; Houldsworth, Jane; Harpaz, Noam
Abstract : Aims: High‐grade appendiceal mucinous neoplasm (HAMN) was recently proposed as a disease entity histologically analogous to low‐grade appendiceal mucinous neoplasm (LAMN), but characterised by high‐grade cytological atypia. The pathogenesis and clinical features of HAMN have not been fully elucidated. Methods and results: Nine cases of HAMN, eight LAMN, 10 appendiceal mucinous adenocarcinomas (MACA) and five appendiceal serrated polyps resected between 2008 and 2017 contributed by three medical centres underwent targeted next‐generation sequencing of 50 cancer‐related genes. The patients in each category had similar profiles with respect to gender, age, tumour stage and follow‐up intervals. Both LAMN and HAMN harboured mutations of KRAS [nine of nine and eight of eight (100%), respectively] and GNAS [five of eight (63%) and five of nine (56%), respectively] in significantly higher proportions than MACA [KRAS, seven of 10 (70%, P  = 0.04); GNAS : one of 10 (10%, P  = 0.02)] and serrated polyps [ KRAS, one of five (20%, P  = 0.0007); GNAS : none of five (0%, P  = 0.04)]. Four cases of HAMN, but none of LAMN, harboured mutations of TP53 [four of nine (44%)] and/or ATM [two of nine (22%)]. Three cases of HAMN (33%) showed extra‐appendiceal spread with retention of the same mutational profiles in the intra‐ and extra‐appendiceal components. The 10 cases of MACA harboured a similar prevalence of TP53 mutations ( n  = 5, 50%) as HAMN but, unlike LAMN and HAMN, some harboured mutations in PIK3CA, APC, FBXW7, PTEN and SMAD4 . Conclusions: HAMN and LAMN share high rates of KRAS and GNAS co‐mutations supporting a common histogenesis and distinguishing them from MACA. Acquisition of TP53 or ATM mutations by HAMN may drive its progression to a more advanced phenotype.